The Relationship Between Cholesterol Levels and Blood Pressure in the Elderly - Pramono, Ardi; Sari, Qoni Ihda Permata (Journal of Community Health Provision, 2025)
Hypertension and hypercholesterolemia are two common comorbidities in the elderly and contribute greatly to the increased risk of cardiovascular disease. The two are often found together, but local data on the direct relationship between the two in the elderly population is limited. The purpose of this study is to find out whether there is a relationship between total cholesterol levels and blood pressure in the elderly. This study uses an observational analytical design with a cross-sectional approach. The subjects of the study were 16 elderly members of the posyandu in Balecatur, Sleman, who met the inclusion criteria. Blood pressure was measured using a sphygmomanometer, and total cholesterol levels were measured using a point-of-care device. Data were analyzed using the chi-square test to determine the relationship between cholesterol levels and hypertension. Of the total 16 respondents, as many as 13 people (81.25%) had blood pressure in the hypertension category, and 13 people (81.25%) had total cholesterol levels ≥200 mg/dL. The results of the statistical test showed that there was a significant relationship between cholesterol levels and blood pressure, with a value of p = 0.018 (p < 0.05). From this study, it was found that there was a significant relationship between cholesterol levels and blood pressure in the elderly. These findings confirm the importance of integrated screening for dyslipidemia and hypertension in promotive and preventive programs in the elderly population.